KONSEP POLITIK ISLAM ALI SYARI’ATI - Sugiyono Sugiyono (Universitas Islam Depok, 2022)
Today's Islamic politics cannot be separated from the role of Islamic political thinkers and actors in the world. Social and political changes that continue to occur in the Islamic world are part of the impact of the widespread influence of earlier Islamic political thought. One of the leading thinkers whose ideas were very broad was Ali Shari'ati. He did not see religion as a scientific specialty or a culture, but he made it an ideology and a school of thought. This means understanding religion as a humanitarian, historical and intellectual movement.